Eficiência e potencial da geração fotovoltaica: estudo de caso da UFSCar frente a outras IES - Andreghetto, Ana Laura Ferraz (Universidade Federal de São Carlos, 2025)
The study analyzes the implementation of photovoltaic systems in higher education institutions (HEIs), focusing on UFSCar’s São Carlos campus. A bibliometric analysis was conducted using the Scopus and Google Scholar databases, employing tools such as Publish or Perish, VOSviewer, and Excel to identify scientific and academic trends regarding the adoption of solar energy in university settings. The results of this analysis were also used to select university campuses globally for case study and comparison with UFSCar's photovoltaic installation. The research thoroughly examined photovoltaic systems at universities in the United Kingdom, Turkey, Spain, the USA, India, and Italy, as these countries stood out in terms of academic output, both in number of publications and citations. This comparative study considered technical, economic, and environmental aspects of the systems, revealing significant variation in installed capacity (from 50 kWp to 4.4 MWp), energy self-sufficiency levels ranging from 12% to 50%, and payback periods between 2 and 11 years, along with different funding models and government incentives, reinforcing the importance of such initiatives. The analysis of UFSCar’s São Carlos campus revealed an annual energy consumption exceeding 8 GWh and presents data from existing initiatives on campus, such as photovoltaic power plants and lighting modernization, which accounted for around 12.5% of the campus's energy consumption in 2022. Furthermore, the analysis identified critical success factors including the need for strategic partnerships and substantial investments, the importance of public policies and government incentives, integration with other sustainability aspects (such as CO2, water, and waste), and the essential engagement of the university community. As main recommendations, the study suggests installing systems on more campus buildings, creating a more complete database on sustainability indicators, increasing monitoring and dissemination of the existing systems, seeking strategic partnerships for expanding the photovoltaic system, and developing a comprehensive sustainability approach on campus. Therefore, it is recommended that UFSCar develop a more comprehensive sustainability strategy, using international experiences as a reference and adapting them to its local reality, considering its specific characteristics and potential.
Efficiency and potential of photovoltaic generation: a case study of UFSCar compared to other HEIs
Keywords: Energia solar fotovoltaica; Universidades sustentáveis; Análise bibliométrica; Transição energética; UFSCar; Photovoltaic solar energy; Sustainable universities; Bibliometric analysis; Energy transition; ENGENHARIAS::ENGENHARIA QUIMICA